1997
DOI: 10.1128/iai.65.6.2145-2152.1997
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Chlamydia trachomatis chronic genital tract infection in gamma interferon gene knockout mice

Abstract: Mice (C57BL/6), treated with progesterone and infected intravaginally with the mouse pneumonitis strain of Chlamydia trachomatis (MoPn), acquired genital tract disease that ascended from the endocervix to the uterine horns, oviducts, and ovaries in a temporal fashion before the occurrence of spontaneous microbiological resolution by about 28 days after infection. Surprisingly, dissemination of MoPn in small numbers to draining lymph nodes, the peritoneal cavity, spleen, liver, kidneys, and lungs occurred in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(122 citation statements)
references
References 33 publications
5
115
1
1
Order By: Relevance
“…C. trachomatis-infected women have higher levels of IFN-c in endocervical secretions than uninfected women [15] and this has also been demonstrated in vivo in murine infection by Chlamydia muridarum [7,16]. Studies using antibody depletion of IFN-c, IFN-c gene knockout mice, or IFN-c receptor gene knockout mice have all shown that IFN-c has a significant role to play in immune defence against various species of chlamydiae [5,6,[17][18][19][20][21]. In various experimental systems, the removal of IFN-c led to higher bacterial loads, reduction in IgG 2a levels, dissemination of infection, failure to resolve disease, and failure to develop protective immunity.…”
Section: Discussionmentioning
confidence: 91%
“…C. trachomatis-infected women have higher levels of IFN-c in endocervical secretions than uninfected women [15] and this has also been demonstrated in vivo in murine infection by Chlamydia muridarum [7,16]. Studies using antibody depletion of IFN-c, IFN-c gene knockout mice, or IFN-c receptor gene knockout mice have all shown that IFN-c has a significant role to play in immune defence against various species of chlamydiae [5,6,[17][18][19][20][21]. In various experimental systems, the removal of IFN-c led to higher bacterial loads, reduction in IgG 2a levels, dissemination of infection, failure to resolve disease, and failure to develop protective immunity.…”
Section: Discussionmentioning
confidence: 91%
“…The VCG delivery vector together with the mouse genital infection model provided a convenient ap-proach for evaluating the immunogenicity and protective efficacy of the bivalent combination vaccine formulation comprising rVCG expressing chlamydial MOMP and HSV-2 glycoprotein D. The results obtained are encouraging, because mice immunized with the combination vaccine were prophylactically protected from genital challenge with high doses of live Chlamydia and HSV-2. An effective combination vaccine against Chlamydia and HSV-2 will most probably need to elicit effective Th1 cellmediated immune responses as well as accessory or neutralizing antibodies (Rank, 1994;Cotter, 1997;Perry et al, 1997;Su, 1997). Significant levels of Th1 responses were induced following immunization, as indicated by the production of high levels of IFN-g compared with IL-4 levels that remained unchanged up to 8 weeks postimmunization.…”
Section: Discussionmentioning
confidence: 99%
“…This is indicated by a decrease in the amount of IFN-g secreted by T cells from mice immunized with the combination vaccine; this formulation contains 50% of the antigen dose present in the single subunit vaccines. High IFN-g and low IL-4 levels are indicative of a Th1 response (Maggi, 1992;Bradley et al, 1995;Igietseme et al, 2003), which has previously been correlated with a degree of protection against both Chlamydia and HSV infections (Rank, 1994;Cotter, 1997;Perry et al, 1997;Su, 1997) (Koelle, 1998;Sin, 1999).…”
Section: Immunized Groupsmentioning
confidence: 99%
“…These results fit naturally into a Th1/Th2 paradigm, with protective immunity ascribed to CD4 T cells making IFN-␥. This narrative was reinforced by the findings that adoptive transfer of Chlamydia-specific Th2 cells (24) and Chlamydia in-fections experimentally skewed toward Th2 responses were accompanied by prolonged and disseminated infection (25)(26)(27)(28). As the cytokine polarization paradigm evolved, these results were extended to include detrimental effects of Th17-skewed responses (29).…”
Section: Cytokine Polarizationmentioning
confidence: 99%